LAMP2 regulates autophagy in the thymic epithelium and thymic stroma-dependent CD4 T cell development. Issue 2 (1st February 2023) - Rodrigues, Pedro M.; Sousa, Laura G.; Perrod, Chiara; Maceiras, Ana R.; Ferreirinha, Pedro; Pombinho, Rita; Romera-Cárdenas, Gema; Gomez-Lazaro, María; Senkara, Meryem; Pistolic, Jelena; Cabanes, Didier; Klein, Ludger; et al.
ABSTRACT: Within the thymus, thymic epithelial cells (TECs) provide dedicated thymic stroma microenvironments for T cell development. Because TEC functionality is sensitive to aging and cytoablative therapies, unraveling the molecular elements that coordinate their thymopoietic role has fundamental and clinical implications. Particularly, the selection of CD4 T cells depends on interactions between TCRs expressed on T cell precursors and self-peptides:MHC II complexes presented by cortical TECs (cTECs). Although the macroautophagy/autophagy-lysosomal protein degradation pathway is implicated in CD4 T cell selection, the molecular mechanism that controls the generation of selecting MHC II ligands remains elusive. LAMP2 (lysosomal-associated membrane protein 2) is a well-recognized mediator of autolysosome (AL) maturation. We showed that LAMP2 is highly expressed in cTECs. Notably, genetic inactivation of Lamp2 in thymic stromal cells specifically impaired the development of CD4 T cells that completed positive selection, without misdirecting MHC II-restricted cells into the CD8 lineage. Mechanistically, defects in autophagy in lamp2 -deficient cTECs were linked to alterations in MHC II processing, which was associated with a marked reduction in CD4 TCR repertoire diversity selected within the lamp2 -deficient thymic stroma. Together, our findings suggest that LAMP2 interconnects the autophagy-lysosomal axis and the processing of selecting self-peptides:MHC II complexes in cTECs, underling its implications for the generation of a broad CD4 TCR repertoire. Abbreviations : AIRE: autoimmune regulator (autoimmune polyendocrinopathy candidiasis ectodermal dystrophy); AL: autolysosome; AP: autophagosome; Baf-A1: bafilomycin A1 ; B2M: beta-2 microglobulin; CTSL: cathepsin L; CD74/Ii: CD74 antigen (invariant polypeptide of major histocompatibility complex, class II antigen-associated); CFSE: carboxyfluorescein succinimidyl ester; CFU: colony-forming unit; CLIP: class II-associated invariant chain peptides; cTECs: cortical TECs dKO: double knockout; DN: double negative; DP: double positive; ENPEP/LY51: glutamyl aminopeptidase; FOXP3: forkhead box; P3 IFNG/IFNγ: interferon gamma; IKZF2/HELIOS: IKAROS family zinc finger 2; IL2RA/CD25: interleukin 2 receptor, alpha chain; KO: knockout; LAMP2: lysosomal-associated membrane protein 2; LIP: lymphopenia-induced proliferation; Lm: Listeria monocytogenes; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MHC: major histocompatibility complex; mTECs: medullary TECs; PRSS16/TSSP: protease, serine 16 (thymus); SELL/CD62L: selectin, lymphocyte; SP: single positive; TCR: T cell receptor; TCRB: T cell receptor beta chain; TECs: thymic epithelial cells; UEA-1: Ulex europaeus agglutinin-1; WT: wild-type.